Knowledge, attitudes and practices related to antibiotic use and resistance patterns among outpatients in Eastern Province, Saudi Arabia - Alramadhan, Waeel Hussain (2015)
Antibiotic resistance is globally responsible for high numbers of morbidity and mortality. Methicillin-resistant Staphylococcus aureus and Extended-spectrum β- lactamases producing Escherichia. coli and Klebsiella. pneumoniae have high prevalence in many countries. Misuse of antibiotic is one major reason that has contributed to the emergence of antibiotic resistance. Knowledge and attitude of antibiotic were determined in some studies in order to determine the practice of antibiotic usage. There is scarce of studies in Saudi Arabia regarding surveillance of antibiotic resistance as well as regarding knowledge, attitude, and practice towards antibiotic usage. The study was carried out to determine the prevalence of MRSA and ESBL-producing E. coli and K. pneumoniae in Qatif Central Hospital for five years. In addition, demographic and clinical characteristics of patients with MRSA and ESBL strains were determined in 2014. Furthermore, questionnaire was carried out to assess the level of knowledge, attitude, and practice towards antibiotics usage among outpatients in Qatif Central Hospital (QCH) and Dammam Medical Complex (DMC), Eastern Province, Saudi Arabia. Microsoft Excel and SPSS were used to analyze antibiotic resistance and the questionnaire. Among the three organisms, the results showed that the prevalence of MRSA among S. aureus was the highest over the five years (2010-2014). The range of MRSA was 21.4% - 30.8%. ESBL-producing E. coli was the second highest prevalence over the five years with a range 14.2% - 26.7%. The prevalence of ESBL-producing K. pneumoniae was low with a minimum of 11.9% and maximum of 20.8%. In 2014, it was shown that majority of MRSA patients were female (59.8%), adults (20-59) years old (47.6%), from ICU (28.0%), and wound samples (38.4%). Likewise, many of ESBL-producing E. coli patients were female (66.7%) and adults (44.4%). Yet, most of patients were from Outpatient Department (34.0%) and urine sample (55.6%). Male patients with ESBL-producing K. pneumoniae were the greater (53.5%) and adults patients were the highest (51.2%). Many patients were from Outpatients Department (30.2%) and wound samples (32.6%). For the cross-sectional survey, out of the 300 respondents, males were 50.7%. Majority were married (73.3%), 18 - 29 years old (47%), college/university education (69.3%), and science field (33%). The findings showed that majority of respondents (79.6%) had low knowledge on antibiotic. Although many respondents (71.7%) had a positive attitude, only few respondents (9.7%) had a good practice towards antibiotic usage. The study showed that level of education (P = 0.002) and field of education (P < 0.0001) were significantly associated with knowledge. Age (P = 0.039), level of education (P = 0.001), and field of education (P < 0.0001) were significantly associated with attitude. Gender (P = 0.026) and level of education (P = 0.006) had associated with practice towards antibiotic usage. In conclusion, prevalence of MRSA and ESBL-producing E. coli was high over the past five years. Respondents in the study showed a low knowledge and poor practice towards antibiotic usage. Interventions are required in order to improve awareness of antibiotic and in turn to decrease antibiotic resistance.